2018
DOI: 10.4046/trd.2017.0042
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of rpoC Mutations in Drug-Resistant Mycobacterium tuberculosis Isolated from Patients in South Korea

Abstract: BackgroundRifampicin (RFP) is one of the principal first-line drugs used in combination chemotherapies against Mycobacterium tuberculosis, and its use has greatly shortened the duration of chemotherapy for the successful treatment of drug-susceptible tuberculosis. Compensatory mutations have been identified in rpoC that restore the fitness of RFP-resistant M. tuberculosis strains with mutations in rpoB. To investigate rpoC mutation patterns, we analyzed 93 clinical M. tuberculosis isolates from patients in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This link between compensatory mutations and strains with rpoB Ser450Leu has been well established (23,25,54,(57)(58)(59)(60). A majority of rpoC mutations identified in our study have been described in previous reports (54,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Many of these mutations are located between codons 431 and 527, a particular region identified as harboring mutations that may compensate for the fitness cost of rpoB resistance mutations (53).…”
Section: Discussionsupporting
confidence: 75%
“…This link between compensatory mutations and strains with rpoB Ser450Leu has been well established (23,25,54,(57)(58)(59)(60). A majority of rpoC mutations identified in our study have been described in previous reports (54,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Many of these mutations are located between codons 431 and 527, a particular region identified as harboring mutations that may compensate for the fitness cost of rpoB resistance mutations (53).…”
Section: Discussionsupporting
confidence: 75%
“…A more recent study by Yun et al . (2018) reported the presence of rpoC mutations in 25.8% of the total isolates 60 . In our study, we found that 8/24 resistant isolates had mutations in rpoC , of which 7 had the S450L dominant mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we identified compensatory mutations that are associated with MDR transmission, such as W848G and I491V in the rpoC gene and T187A in the rpoA gene. (3,(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%